Islam Dan Studi Agama-Agama Di Indonesia - Roro Sri Rejeki Waluyajati; Herlina Nurani (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2016)
The purpose of this study was to determine the problems faced by the Department of Comparative Religion in Indonesia especially in UIN, Bandung, Jakarta and Yogyakarta. The problems could be experienced by the students or by the department, in both academic field and student affairs, besides among academic authors also wish to express how the perspective of rural communities, in the village area of West Bandung Cibenda about majoring in comparative religion, is it true this course can not be accepted by society, especially rural areas? The results showed that there was strong relationship between exclusive religious attitudes and religious conflict in society. The exclusive attitude could trigger conflict easily. In this situation, the existence of the Department of Comparative Religion is needed, as an academic medium which task is to produces mediators,  who can reduce or reconcile religious conflicts through mainstreaming inclusive and pluralist religious attitudes in society,  Unfortunately, the existence of this Department has not been promoted well. So that, people has not perceive this department well.